IKZF1plus is a frequent biomarker of adverse prognosis in Mexican pediatric patients with B-acute lymphoblastic leukemia - Garcia-Solorio, Joaquin; Núñez-Enriquez, Juan Carlos; Jiménez-Olivares, Marco; Flores-Lujano, Janet; Flores-Espino, Fernanda; Molina-Garay, Carolina; Cervera, Alejandra; Casique-Aguirre, Diana; Peñaloza-Gonzalez, José Gabriel; Baños-Lara, Ma. Del Rocío; García-Soto, Ángel; Galván-Díaz, César Alejandro; et al. (Frontiers in Oncology, 2024)
Background: Recurrent genetic alterations contributing to leukemogenesis have been identified in pediatric B-cell Acute Lymphoblastic Leukemia (B-LLA), and some are useful for refining classification, prognosis, and treatment selection. IKZF1 plus is a complex biomarker associated with a poor prognosis. It is characterized by IKZF1 deletion coexisting with PAX5, CDKN2A/2B, or PAR1 region deletions. The mutational spectrum and clinical impact of these alterations have scarcely been explored in Mexican pediatric patients with B-ALL. Here, we report the frequency of the IKZF1 plus profile and the mutational spectrum of IKZF1, PAX5, CDKN2A/2B, and ERG genes and evaluate their impact on overall survival (OS) in a group of patients with B-ALL.Methods: A total of 206 pediatric patients with de novo B-ALL were included. DNA was obtained from bone marrow samples at diagnosis before treatment initiation. A custom-designed nextgeneration sequencing panel was used for mutational analysis. Kaplan-Meier analysis was used for OS estimation.We identified the IKZF1 plus profile in 21.8% of patients, which was higher than that previously reported in other studies. A significantly older age (p=0.04), a trend toward high-risk stratification (p=0.06), and a decrease in 5-year Overall Survival (OS) (p=0.009) were observed, although heterogeneous treatment protocols in our cohort would have impacted OS. A mutation frequency higher than that reported was found for IKZF1 (35.9%) and CDKN2A/2B (35.9%) but lower for PAX5 (26.6%). IKZF1 MUT group was older at diagnosis (p=0.0002), and most of them were classified as highrisk (73.8%, p=0.02), while patients with CDKN2A/2B MUT had a higher leukocyte count (p=0.01) and a tendency toward a higher percentage of blasts (98.6%, >50% blasts, p=0.05) than the non-mutated patients. A decrease in OS was found in IKZF1 MUT and CDKN2A/2B MUT patients, but the significance was lost after IKZF1 plus was removed.Discussion: Our findings demonstrated that Mexican patients with B-ALL have a higher prevalence of genetic markers associated with poor outcomes. Incorporating genomic methodologies into the diagnostic process, a significant unmet need in low-and mid-income countries, will allow a comprehensive identification of relevant alterations, improving disease classification, treatment selection, and the general outcome.